2013
DOI: 10.1099/mic.0.067025-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiple rRNA operons are essential for efficient cell growth and sporulation as well as outgrowth in Bacillus subtilis

Abstract: The number of copies of rRNA (rrn) operons in a bacterial genome differs greatly among bacterial species. Here we examined the phenotypic effects of variations in the number of copies of rRNA genes in the genome of Bacillus subtilis by analysis of eight mutant strains constructed to carry from two to nine copies of the rrn operon. We found that a decrease in the number of copies from ten to one increased the doubling time, and decreased the sporulation frequency and motility. The maximum levels for transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
64
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 37 publications
7
64
0
Order By: Relevance
“…In contrast, we observed that B. subtilis encapsulated in mPEG-PDLLA are capable of proliferating in an exponential fashion with an estimated doubling time of approximately 25 minutes. This is in close agreement with the minimum doubling time of 21 minutes reported for B. subtilis under optimal growth conditions (Yano et al 2013). …”
Section: Discussionsupporting
confidence: 91%
“…In contrast, we observed that B. subtilis encapsulated in mPEG-PDLLA are capable of proliferating in an exponential fashion with an estimated doubling time of approximately 25 minutes. This is in close agreement with the minimum doubling time of 21 minutes reported for B. subtilis under optimal growth conditions (Yano et al 2013). …”
Section: Discussionsupporting
confidence: 91%
“…6A). The decrease in the number of rrn operons correlated with the reduction in the amount of ribosomes as well as the reduction in the growth rate (61,62). These results suggest that the Mg 2ϩ content in the cell is influenced by the amount of ribosomes present, especially 70S ribosomes and polysomes.…”
Section: Resultsmentioning
confidence: 62%
“…When the 50S and 30S subunits were included with the 70S ribosomes and polysomes, the total areas of the peaks were 89%, 77%, and 80% of the wild-type area in the ⌬rplA, ⌬rplW, and ⌬rpmH mutants, respectively. Previously, we have constructed mutants that harbor one to nine copies of the rrn operon in their genome (the wild type contains 10 copies) and confirmed that the number of ribosomes is reduced in these mutants, especially in those that harbor only one or two rrn operons (61,62). In the present study, we determined the cellular Mg 2ϩ content in these mutants and found that the Mg 2ϩ content decreased as the number of rrn operons decreased (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Condon et al (1995) used Escherichia coli with multiple rRNA operons inactivated by antibiotic cassettes to demonstrate that the number of rRNA operons in the genome affects cell proliferation rate. Yano et al (2013) found that the existence of multiple rRNA operons underlies the high growth rate of Bacillus subtilis . Another study reported that the copy number of rRNA operons on the genomes is correlated with growth rate of the prokaryotes under optimal culture condition (Vieira-Silva and Rocha, 2010; Roller et al, 2016).…”
Section: Resultsmentioning
confidence: 99%